EVALUATION OF SPECIFIC METHODS TO DETECT CRACK AND DAMAGE OF MECHANICAL BEAM STRUCTURES USING FREE VIBRATION ANALYSIS (Journal of Engineering, 2024)
The importance of the beam in the service of our life and how the damaged beam costly influence the economy and even endanger the human life itself, draws our attention to study the specific methods to detect crack and damage by using free vibration analysis of mechanical beam structures. In the present research, three kinds of beam structures have been investigated namely (simply supported beam, portal frame and crane frame) by using finite element method. Six cases of damage are modeled for simply supported beam and portal frame and with seven cases for crane frame. The damage is simulated by reducing the stiffness of assumed elements with ratios (25% and 50 %) in mid- span of the simply supported beam and by introducing cracked elements at different locations with ratio of depth of crack to the height of the beam (a/h) 0.1, 0.25 for simply supported beam and 0.1 and 0.2 for portal and crane frames. A program coded in Matlab 6.5 was used to model the numerical simulation of the damage scenarios. The results showed a decreasing in the five natural frequencies with shifting in the damaged mode shape associated with their frequencies from undamaged beam which means the indication of presence of the damage. The direct comparison gives an indication of the damage but the location of the damage, is not detected. Four structural damage identification methods based on changes in the dynamics characteristics of the beam structures are examined and evaluated for damage scenarios for the three structures considered. The results of the analysis indicate that the curvature energy damage index method performs well in detecting, locating and quantifying damage in single and multiple damage scenarios for the three structures.